Performance of Thin-Tailed Sheep Fed Cassava Peel Silage-Based Diet with Different Protein Supplements - Mashudi; Kusmartono; Ndaru, P. H.; Kartika, A. D. (Tropical Animal Science Journal, 2024)
Growing sheep using native grass or crop byproducts has been commonly practiced by farmers in East Java, Indonesia. Better growth rates can be achieved when protein and energy sources are combined in the ration. This study aimed to evaluate the effect of feeding cassava peel silage (CPS) and different protein sources on the growth of sheep fed a maize stover-based diet. Twenty-four growing sheep aged 8-10 months and weighing 17.24 ± 1.87 kg were used, and they were kept in individual cages that allowed the measurements of feed intake, feces, and urine secreted per animal. The treatments applied were T1: rice bran (0.75% BW)+Urea (2% CPS); T2: (50% rice bran + 50% copra meal in 1.5% BW); T3: cassava leaf hay (1% BW); and T4: sunflower leaf hay (1% BW). All treatments provided maize stover (MS) at 0.5% of body weight and CPS ad libitum. The variables measured were nutrient intake and digestibility, rumen fermentation, and live weight gain (LWG). The results revealed that the treatments had a significant increase (p<0.01) in the digestibility of CP, EE, CF, NDF, and ADF and reduced the amount of methane gas (CH4). Additionally, the treatments had a significant increase (p<0.01) in some variables such as N retention, LWG, and reduced FCR. Furthermore, the treatments significantly increased (p<0.05) NH3, propionic acid, and the C2/C3 ratio, but they did not have a significant effect on pH, acetic acid, or butyric acid content. In summary, the T3 treatment improved live weight gain (LWG) and decreased the feed conversion ratio (FCR) in thin-tailed sheep.